Implementasi Metode Eksperimen Verifikasi di Laboratorium untuk Meningkatkan Motivasi dan Hasil Belajar Biologi Peserta Didik pada Materi Ekosistem - Ni Nyoman Parmithi; Anak Agung Istri Mirah Dharmadewi; Ni Putu Widiani (FPMIPA IKIP PGRI Bali, 2018)
Effective and efficient learning methods need to be developed in order to motivate students to improve learning outcomes. One way to motivate students to learn biology through experimental verification methods in the laboratory. This study aims to increase motivation and learning outcomes of biology. The type of research used is classroom action research. The research subjects were class students X MIPA 4 SMA N 1 Mengwi school year 2017/2018, 35 people. The object of this research is learning motivation by using questionnaires and learning outcomes using multiple choice tests. Data were analyzed using descriptive statistical analysis. The results of data analysis showed an increase in the value of learning outcomes in the first cycle to the second cycle, namely the first cycle an average of 74.57, the second cycle to 82.28, the absorption of the first cycle 74.57% in the second cycle 82.28%, and completeness classical cycle I 80% in cycle II 97.14% was declared successful. Analysis of learning motivation data in the first cycle and second cycle shows the High category (T), so the cycle is stopped. It was concluded that the implementation of the verification experiment method in the laboratory could increase the motivation and learning outcomes of class students X MIPA 4 SMA N 1 Mengwi school year 2017/2018.